1976
DOI: 10.1107/s0021889876010790
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the structures of amorphous and liquid Ag–Cu and Cu–Mg alloys

Abstract: Amorphous films of AgCu and CuMg2, approximately 3000 A in thickness, were prepared by co-evaporation of Ag and Cu, and Cu and Mg, respectively, onto 25 #m thick Be sheets, held at liquid nitrogen temperature. Mo K~ X-rays were used as a radiation probe to determine the structure of the films, at room temperature, and of the liquid alloys of Cu with 50 at.~ Ag and with 0 and 67 at.~o Mg at 50°C above the liquidus temperature. With the transmission technique, the interference functions (or structure factors) I(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In many works, the strong inter-atomic interaction and the formation of associations in the liquid state were related to the high GFA [5,7,[11][12][13][14][15]. Audebert et al [5] observed in the amorphous alloys of Mg-Cu-RE, an amorphous pre-peak in the X ray diffractogram at Q = 1.50 Å −1 (Q: scattering vector), similar to that observed for the Mg 2 Cu amorphous alloy [16]. They proposed that the strong interaction between Mg and Cu atoms produces associations like Mg 2 Cu in the liquid, which increases the viscosity and the GFA of this alloy.…”
Section: Introductionsupporting
confidence: 53%
“…In many works, the strong inter-atomic interaction and the formation of associations in the liquid state were related to the high GFA [5,7,[11][12][13][14][15]. Audebert et al [5] observed in the amorphous alloys of Mg-Cu-RE, an amorphous pre-peak in the X ray diffractogram at Q = 1.50 Å −1 (Q: scattering vector), similar to that observed for the Mg 2 Cu amorphous alloy [16]. They proposed that the strong interaction between Mg and Cu atoms produces associations like Mg 2 Cu in the liquid, which increases the viscosity and the GFA of this alloy.…”
Section: Introductionsupporting
confidence: 53%
“…This could be a consequence of an intensification of the chemical heterogeneity of the amorphous structure or the formation of small fraction of crystalline order at the nanoscale. In addition, the diffractograms of the Y and Al-0 showed a weak and broad pre-peak around 2θ~20.3 o , which reveals a strong chemical short and medium range order, as it was observed in the literature 22,28,29 . The X-ray diffractograms of the Al-5 and Al-10 alloys do not show a clear pre-peak, which is in agreement with the criterion of the micro-alloying to reduce the fraction of the strong hetero-atomic clusters in the amorphous phase.…”
Section: Microstructural Characterisationmentioning
confidence: 54%
“…[15] Thus, the Gibbs free energy of the liquid phase is given by The interaction energies ð L liq i;j Þ are described here as constants, while the Gibbs free energies of formation ðDG liq Cu m Mg n ) are described as functions of temperature, using the form given in Eq 1. Where sufficient heat capacity data are available, the parameters a)e are used.…”
Section: The Liquid Phasementioning
confidence: 99%
“…First, in each of these treatments, the liquid phase is modeled as a regular solution, a model that cannot describe the chemical ordering observed in this system. For example, X-ray diffraction experiments reported by Lukens and Wagner [15] indicate the existence of chemical short range order in the liquid phase with Cu 2 Mg and CuMg 2 stoichiometries. This discrepancy is clearly observed in the inability of these models to accurately describe the heat capacity of the undercooled liquid, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%